A systematic review of coping strategies in parents of children with attention deficit hyperactivity disorder (ADHD). (March 2020) - Craig, Francesco; Savino, Rosa; Fanizza, Isabella; Lucarelli, Elisabetta; Russo, Luigi; Trabacca, Antonio
Highlights: Parents of ADHD children used more dysfunctional coping styles than those of TD. The most commonly used strategy by parents of children with ADHD seems to be avoidant-focused coping. Mothers of ADHD children sought more support than mothers of TD children. Review illustrates the need to adapt psychoeducational interventions for parents of ADHD children. Abstract: Background: Parents of children with attention deficit hyperactivity disorder (ADHD) use several coping strategies to deal with ADHD symptoms impacting family life. Aim: The aim of this systematic review was to summarize the coping strategies used by parents of children with ADHD, identify which tools are most frequently used to measure coping strategies, and examine factors influencing parental coping. Method: According to PRISMA guidelines, we searched for articles indexed in PubMed, EBSCOhost, Scopus, and Web of Science using a combination of expressions including "coping" AND "ADHD" OR "attention-deficit/hyperactivity disorder" AND "parent" OR "parenting" OR "caregiver". Results: Fourteen empirical studies were identified as relevant to our research. Many different types of tools are used to assess coping strategies. We found that parents of ADHD children used more avoidant-focused coping strategies than parents of typical children. Mothers of ADHD children sought significantly more support and used more indirect means than mothers of typically developing (TD) children. Conclusions: This review underlines the importance of further exploring coping mechanisms of parents of children with ADHD in order to promote positive coping strategies for parents of children with ADHD, and to help such parents to identify people who can support them.